PENGARUH KOMUNIKASI PEMASARAN YANG DILAKUKAN OLEH DOSEN TERHADAP MINAT BACA MAHASISWA PADA PERPUSTAKAAN PERGURUAN TINGGI NEGERI DI JAKARTA SELATAN - Surya Adi Sasmita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
The College Library was established to support academic needs both for the internal public and the external public of the college itself. However, the development of communication technology has made the interest in reading students in college libraries decrease. Therefore college libraries must implement the right strategies to increase students' reading interest in the library. Through this study, researchers found the influence of marketing communication strategies carried out by lecturers (variable x) on students' reading interest (variable y) by 72%. This shows that lecturers should also provide socialization and direction to students related to the importance of reading reference sources from campus libraries by telling interesting things so that students' reading interest in college libraries increases librarians in college libraries can make lecturers as co-workers in carrying out lecturer marketing communication strategies considering are individuals whose daily life is more interact with students so that lecturers have an important role in carrying out library marketing communication to students.